Effects of foreign direct investment on climate change in the Asian region - Ehsanullah (Economic Journal of Emerging Markets, 2024)
Purpose ― This research aims to empirically investigate and compare the effects of foreign direct investment on climate change in five South Asian nations.Methodology ― This research uses yearly data covering 1980–2020 in five South Asian nations: Bangladesh, India, Nepal, Pakistan, and Sri Lanka. Vector Autoregressive (VAR) methods with variance decomposition and impulse response function provide the basis of the empirical data for comparison analysis. Findings ― This research shows that foreign direct investment's impact on pollution ranges from 1% to 10% in four countries and 16.13% in Pakistan. This indicates that in five South Asian states, there is little endogenous correlation between foreign direct investment and pollution. Furthermore, a shock to foreign investment improves the environmental conditions in Bangladesh and India while harming the growth of other nations.Implications ― The impact of foreign direct investment on pollution may vary based on each country's economic situation. Public efforts to enhance capital goods, education, health, and infrastructure are essential for reducing pollution and attracting foreign investment. Therefore, improved transparency and governance are essential for a positive relationship between growth and foreign investment.Value/Originality ― This research contributes to analyzing and comparing the effects of foreign direct investment on climate change in five South Asian nations using Vector Autoregressive (VAR) methods.